2018
DOI: 10.1007/s00417-018-3955-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term database analysis of conventional and accelerated crosslinked keratoconic mid-European eyes

Abstract: In a large mid-European study population including subgroup analysis of mild and moderate keratoconus, accelerated CXL showed similar results to conventional CXL regarding keratometry, corneal topography indices, and CDVA, but further improvement of UDVA. Preoperative Kmax did not affect the postoperative course of corneal topography indices and TCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…However, other studies have demonstrated that both procedures have a comparable effect in stabilizing keratometry. 51,52 It is of note that typically both SCXL and ACXL are generally preceded with epithelial removal (epithelium-off CXL), although investigations have been conducted to explore the potential influence on clinical outcomes between epithelium-off and transepithelial (epithelium-on) procedures using both SXCL and ACXL protocols. 53,54 In an attempt to try to clarify the potential benefits of CXL, we undertook this current meta-analysis to compare the effectiveness and safety of ACXL in comparison to SCXL.…”
mentioning
confidence: 99%
“…However, other studies have demonstrated that both procedures have a comparable effect in stabilizing keratometry. 51,52 It is of note that typically both SCXL and ACXL are generally preceded with epithelial removal (epithelium-off CXL), although investigations have been conducted to explore the potential influence on clinical outcomes between epithelium-off and transepithelial (epithelium-on) procedures using both SXCL and ACXL protocols. 53,54 In an attempt to try to clarify the potential benefits of CXL, we undertook this current meta-analysis to compare the effectiveness and safety of ACXL in comparison to SCXL.…”
mentioning
confidence: 99%
“…Inc., Waltham, MA) recommends intermittent application of isotonic riboflavin every two minutes for ten minutes. However recent studies reported different clinical efficacies with various application times of riboflavin (10-30 minutes) and intervals (two to five minutes) in the accelerated protocol [8][9][10][11]18]. Shorter application times (every two minutes for 10 minutes) seem to have lower efficacy, even in pulsed-light accelerated protocol, than that of the conventional protocol [11].…”
Section: Introductionmentioning
confidence: 99%
“…To shorten the procedure, an accelerated cross-linking protocol was introduced; it uses a shorter radiation time with greater intensity based on the Bunsen-Roscoe law of reciprocity [6]. However, there are debates about whether the accelerated protocol has an effect equivalent to that of the conventional protocol according to different protocols of irradiation and riboflavin application [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Its biological effect is proportional to the energy delivered. Surgical procedure of accelerated protocol is basically the same as the standard Dresden protocol except two aspects; the intensity (from 9 to 30mW/cm2) and irradiation time of UV-A (from 3 to 15 minutes) [8][9][10][11][12][13][14][15][16]. Many studies have reported that clinical results of the accelerated protocol are comparable to those of the standard Dresden protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Inc., Waltham, MA, USA) recommends intermittent application of isotonic riboflavin every two minutes for a total of ten minutes. Recent studies have reported different clinical efficacies with various application time (from 10 to 30 minutes) and intervals (two to five minutes) [9][10][11][12]19]. Shorter application time (every two minutes for 10 minutes) seems to have lower efficacy, even in pulsed-light accelerated protocol, than the standard protocol [12].…”
Section: Introductionmentioning
confidence: 99%